Case reports: An aggressive central giant cell granuloma of the jaws in two pediatric patients - Adewale O. Adesina; Mofoluwake A. Ladeji; Taofiq O. Opaleye; Alonge Moradeke; Rasheedat Ojikutu; Ajibola Y. Salami; John C. Wemambu (Elsevier, 2021)
Central giant cell granuloma (CGCG) is a relatively uncommon and benign, non-neoplastic jaw lesion which occurs in children and young patients. It has been classified into two types based on its clinico-radiologic features into a slow growing asymptomatic, nonaggressive lesion, and an aggressive type encountered in younger patients growing rapidly into a large size, perforating the cortex, causing root resorption, and has a tendency to recur. Approximately 70% have the biological behavior of a non-aggressive, asymptomatic, slow-growing lesion, whereas the remaining 30% show an aggressive, progressively destructive behavior. However, care should be used to differentiate aggressive and non-aggressive granulomas. Histologically, aggressive lesions show a large area occupied by giant cells, great size, greater nucleolar organization and high expression of CD34 adhesion factors. Many surgeons choose the surgical treatment, which can be curettage, wide excision or resection with safety margins depending on the extent and behavior of the lesion as their preferred treatment option. We report two cases of aggressive central giant cell granuloma in pediatric patients, the clinical presentation and its treatment.